The drivers of debt financing within state-owned corporations in South Africa - Nyamita, Micah Odhiambo; Dorasamy, Prof. Nirmala (Archives of Business Research, 2021)
The public sector financial management reforms being adopted by many countries, such as South Africa, have encouraged the adoption of private-sector management style, such as debt management, within the state-owned corporations. The reform agenda on debt financing is that state-owned corporations should face competitive conditions regarding access to finance. To highlight on the achievements of these reforms, this study explored the questions as to whether the drivers of debt financing within state-owned corporations in South Africa are similar to those of private-sector corporations. Applying a hybrid of cross sectional and longitudinal quantitative surveys, a panel data regression model was used to analyse data from 26 income-generating state-owned corporations in South Africa for the eight-year period 2007-2014 using the generalized method of moments (GMM). The results identified the main determinants of debt financing within the state-owned corporations in South Africa to include asset tangibility, corporation’s growth and liquidity.